Pendekatan Strategis dalam Persaingan: Interdependensi Finansial Amerika Serikat dan Tiongkok - Zulaekha Amalia (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2021)
China has become a challenge to the advancement of the United States. This is supported by facts that show the great dependence of the United States. Through China's financial and economic power, China was able to lock in the power of the United States in the international system. This condition can be a dangerous threat if the power is used as state instrument. Therefore, this article will aim to show how China's financial and economic influence can pose a threat to the United States and the world. Then, this article will present the financial interdependence that is viewed through the immense debt of the United States to China and its relation to world trade and an analysis of the threats caused by these powers. This article uses the concept of Power and Interdependence as described by Robert O. Keohane and Joseph S. Nye Jr. to be an analytical framework. This research is qualitative research based on case studies, which is reviewed through literature review from related data sources. The findings in this article show that China does indeed have a major influence on the sustainability of the United States and inevitably the two countries must have strong interdependence due to the threats they face.